A Review Study of the Influences of Dendrimer Nanoparticles on Stored Platelet in Order to Treat Patients (2001-2020) - Mehrizi, Tahereh Z.; Ardestani, Mehdi Shafiee; Kafiabad, Sedigheh Amini (Current Nanoscience, 2022)
Background: Platelets are sensitive to chilling, so the optimal storage temperature for maintaining normal function and structure in platelets is 22-24 °C up to 3-5 days. Introduction: Platelets are important blood cells involved in immunity, inflammation, and thrombosis. Today, platelet products are widely used to prevent bleeding in patients with thrombocytopenia and coagulopathy disorders. As a result, maintaining the quality of these products is very important. Methods: In this review study, the reported influences of various dendrimers on platelets from 2001 to 2020 were investigated. Results: The results showed that positively charged dendrimers can cause platelet aggregation and activation during platelet storage time through their amine residues. In addition to surface charge, high generations, molecular weight and concentration are not recommended in the field of platelet storage and treatment. In contrast, negatively charged dendrimers, usually used at lower generations with proper molecular weight, lower size (less than 100 nm) and their carboxyl residues, cannot induce adverse effects on platelets during storage time. In addition, the results of this study revealed that PEGylation of dendrimers and platelets can improve platelet storage conditions. Conclusion: As anionic dendrimers can improve platelet storage time without inducing significant changes in morphology and function of platelets, they are recommended in the field of platelet storage and treatment.
Keywords: platelet products